Prevalence of smoking among patients treated in NHS hospitals in England in 2010/11: a national audit - Szatkowski, Lisa; Murray, Rachael; Hubbard, Richard B.; Agrawal, Sanjay; Huang, Y.; Britton, John (BMJ Publishing Group, 2015)
Using data from The Health Improvement Network and Hospital Episode Statistics, we investigate smoking prevalence, number of smokers treated and opportunities for cessation intervention among patients treated in National Health Service (NHS) hospitals in England from April 2010 to March 2011. Our results show that approximately 1.1 million smokers are treated in English hospitals each year, receiving a total of 2.6 million episodes of care. These findings suggest that delivering smoking cessation as a routine component of hospital care, as recommended by recent National Institute for Health and Care Excellence guidance, could achieve marked reductions in the prevalence of smoking and improve the cost-effectiveness of NHS hospitals.